SOIL POLLUTION AND HEAVY METAL CONTAMINATION: INSIGHT FROM EFFLUENT DISCHARGED FROM CHALLAWA INDUSTRIAL AREA, NIGERIA - Darma, Aminu Inuwa; Zakari, Shamsu Ado; Sani, Ali; Mamman, Halimma Sani (FUDMA JOURNAL OF SCIENCES, 2024)
The discharge of industrial wastewater represents a significant source of environmental pollution, particularly in developing regions where regulatory enforcement is often insufficient. This study examined the chemical characteristics of effluent discharged from three locations (LA, LB, and LC) close to the Challawa Industrial Area in Kano, Nigeria, and determined their effects on nearby soil. Effluent samples were analysed for pH, biochemical oxygen demand (BOD), phosphates (PO), nitrates (NO-N) and critical toxic heavy metals (HMs) such as lead (Pb), chromium (Cr), copper (Cu), Zinc (Zn) and cadmium (Cd). Simultaneously, soil samples from three locations near the discharge point were evaluated for pH, total nitrogen (TN), and total phosphorus (TP). The results revealed that effluent concentrations of HMs and nutrients far exceeded the permissible limits of the National Environmental Standards and Regulations Enforcement Agency. The Pb (90.79 mg/L), Cd (10.06 g/L), Zn (33.43 mg/L), Cr (4.49 mg/L), and Cu (12.76 mg/L) concentrations were well above the regulatory limits of 0.05 mg/L, 0.01 mg/L, 0.05 mg/L, 0.01 mg/L, and 0.02 mg/L, respectively. The Phosphate (299.74 mg/L) and nitrate (381.97 mg/L) levels also exceeded NESREA standards, indicating a significant risk of eutrophication in nearby water bodies. Regression analysis revealed that higher pH tended to increase the concentration of both nutrients, with P showing a more consistent and stronger association (p
Keywords: Effluent discharge; NESREA compliance; Challawa industrial area